12 MAP4K4 as a Therapeutic Target in Cardiomyocyte Death: Novel inhibitors Identified through Pharmacophore Modelling and Virtual Screening. (19th January 2014) - Fiedler, L R; Chapman, K; Guo, W; Kanaganayagam, S; Low, C; Traulau-Stewart, C; Schneider, M D
Abstract : Ratonale: Though reperfusion therapies have transformed treatment of myocardial infarction, no established treatments directly address the problem of cardiac cell death. At the level of organ function, attenuating acute or chronic cell death would preserve cardiac pump function and suppress progression to heart failure. We previously identified MAP4K4/HGK as an activator of the TAK1 – JNK pathway in cardiac cell death, whose inhibition by dominant-negative mutations or shRNA knockdown confers protection in culture. To address this therapeutic potential and further dissect the mechanisms by which MAP4K4 mediates cardiomyocyte death, we initiated a small molecule discovery programme. Results: An in-house library of 2000 compounds was screened for inhibition of recombinant human MAP4K4 kinase domain. Eight showed a pIC50 > 5, and the top four were taken forward. Hits were analysed by 3D field point modelling (Cresset) to identify features of similar charge distribution. Three inhibitors fitted a consensus pharmacophore model, used to interrogate 2.5 M structures in silico, from which 40 were tested for inhibition of MAP4K4. Selectivity of the top two was tested both against a panel of >140 human kinases and against the kinome in situ, using cell lysates. Relative to the only known MAP4K4 inhibitors, these exhibited equal potency (IC50 35-100 nM) but greater specificity (3-5 kinases inhibited >50% at 1 uM) and lack of toxicity in cardiomyocytes. Conclusions: We have successfully employed pharmacophore modelling and virtual screening to leverage an initial screen for novel MAP4K4 inhibitors, and obtained promising lead compounds for optimisation and experimental studies.